Analisis Penerapan Unsur Total Quality Management (TQM) pada Unit Rekam Medis di Puskesmas Guntung Manggis - Ni Wayan Kurnia Widya Wati; Khairunnisa Khairunnisa (HB PRESS, 2023)
Puskesmas is a health service facility that organizes public health efforts and individual health efforts at the first level, by prioritizing promotive and preventive efforts in their working areas. To be able to realize superior quality health services, health institutions must implement and implement TQM. The purpose of this study is to implement the elements of Total Quality Management (TQM) at the Guntung Manggis Health Center based on teamwork, education and training and continuous system improvement. This type of research is descriptive research. The sample in this study were medical record officers, totaling 5 people. The implementation of the Total Quality Management element based on teamwork at the Guntung Manggis Health Center, namely the element of teamwork has been implemented and carried out. The implementation of the Total Quality Management based on education and training at the Guntung Manggis Health Center, namely the educational element with a D3 background in medical records, is only 1 person and training has been implemented through seminars, training and development which are attended by every employee in the medical record unit to grow knowledge, abilities and employee skills. The implementation of the Total Quality Management element based on a continuous system at the Guntung Manggis Health Center, namely the element of continuous system improvement has been implemented but there are still obstacles, namely the lack of improvement of supporting facilities (facilities and infrastructure) for services at the health center.